Late-stage derivatization of a (B, O)2-doped perylene. Issue 35 (22nd August 2022) - Ouadoudi, Omar; Kaehler, Tanja; Çevik, Enes Görkem; Bolte, Michael; Stöger, Berthold; Virovets, Alexander; Lerner, Hans-Wolfram; Wagner, Matthias
Abstract : Regioselectively di- and tetrabrominated (B, O)2 -perylenes were prepared and used in Stille-type couplings to afford highly luminescent alkynylated derivatives. Abstract : Regioselective di- and tetrabrominations of the (B, O)2 -perylene 1 afford derivatives 2–4 . Despite their poor solubility, 2 and 4 could be used in Stille-type coupling reactions to introduce two CCMe (5 ) or four CC( p -C6 H4 t Bu) substituents (6 ), respectively. The alkynylated derivatives show blue-green photoluminescence with appreciable quantum efficiencies.